The 2015 Newfoundland and Labrador Election: Liberals Have a Ball as PC Party Suffers from Post-Williams Hangover - Marland, Alex (c/o Institute for Governance Studies, Simon Fraser University, 2016)
From 2003 to 2010, Premier Danny Williams maintained a tight grip on the Progressive Conservative (PC) Party of Newfoundland and Labrador and the provincial government. His chosen successor Kathy Dunderdale carried the party to a third consecutive majority government in 2011. But the new energy of her leadership masked serious cracks in the PC Party foundation. Barely two years into her mandate, Premier Dunderdale resigned, setting in motion further political instability as the party fumbled to replace her. All the while, Dwight Ball and the Liberal Party won by-election after by-election, public opinion poll after poll. That the Liberals would form the government after the 2015 general election was a certainty; that the opposition won so many seats in a smaller legislature was the surprise. Early in his tenure, Premier Williams often remarked that he was responsible for cleaning up the economic mess left by the previous administration. With growing budget deficits stemming from overspending, coupled with declining offshore oil revenues, the economic problems and difficult decisions awaiting Premier Ball and the Liberal government are just as ominous.